Big little lies - Moriarty, Liane (New York : G. P. Putnam's Sons, 2014)
Follows three mothers, each at a crossroads, and their potential involvement in a riot at a school trivia night that leaves one parent dead in what appears to be a tragic accident, but which evidence shows might have been premeditated.
"Amy Einhorn Books."
Keywords: Parents -- Fiction; Murder -- Fiction; Schools -- Fiction; Suburbs -- Fiction; Families -- Fiction; Divorce -- Fiction; Mothers -- Fiction; Domestic fiction; Psychological fiction; Mystery fiction